Increasing the crack resistance of high-strength self-compacting concrete - Troуan, Vyacheslav; Kindras, Bogdan (Technology audit and production reserves, 2021)
The object of research is high-strength self-compacting concrete, which does not require additional vibration during laying. One of the most problematic issues of high-strength self-compacting concretes is increased cracking, associated with large shrinkage deformations of such concretes and their fragile destruction. A decrease in shrinkage deformations of concrete was established when part of the cement was replaced to mineral additives. This effect is explained by a decrease of the cement content and, accordingly, a decrease of the chemical component of the autogenous shrinkage of concrete, and an increase of the adsorptive binding of capillary moisture by mineral additives, with reduces the physical drying shrinkage of concrete. In this case, the type and dispersion of the used mineral additive can affect to the shrinkage deformations of concrete. A significant decrease in shrinkage deformations when using metakaolin is explained by an increase the amount of ettringite as a result of the reaction of active metakaolin Al2O3 with two-water gypsum of cement. It was found that the replacement of cement to 10 % of mineral additives leads to a decrease in the value of the critical stress intensity factor (SIF), which is compensated by a decrease of the fragility of concrete fracture (an increase of the area of microplastic deformations). At the same time, the type of mineral additive used does not affect to the value of the critical stress intensity factor, but significantly affects to the fragility of fracture of concrete samples. The introduction of 10 % mineral additives (to replace cement) had a positive effect on the retention of flow of self-compacting concrete mixes; the best results according to this criterion were observed when using silica fume, fly ash and limestone. All mineral modifiers, except for silica fume, led to a decrease of the compressive strength of high-strength concretes on all terms of hardening. In the case of the tensile strength of concrete at bending and splitting, with the introduction of silica fume, metakaolin and fly ash, a positive effect was observed compared to the base composition without additives. Comprehensive accounting of the results obtained will allow a reasonable approach to the design of high-strength self-compacting concretes with increased crack resistance.